Grid Computing 2008
DOI: 10.1007/978-0-387-09457-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating The Size Of Peer-To-Peer Networks Using Lambert's W Function

Abstract: In this work, we address the problem of locally estimating the size of a Peerto-Peer (P2P) network using local information. We present a novel approach for estimating the size of a peer-to-peer (P2P) network, fitting the sum of new neighbors discovered at each iteration of a breadth-first search (BFS) with a logarithmic function, and then using Lambert's W function to solve a root of a ln(n) + b − n = 0, where n is the network size. With rather little computation, we reach an estimation error of at most 10 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 18 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…In this work, we modify the W algorithm of Bustos et al [2] seeking higher generality and efficiency. First, we modify the proposed BFS procedure by including two stopping criteria to be examined after each iteration.…”
Section: Proposed Solutionmentioning
confidence: 98%
See 3 more Smart Citations
“…In this work, we modify the W algorithm of Bustos et al [2] seeking higher generality and efficiency. First, we modify the proposed BFS procedure by including two stopping criteria to be examined after each iteration.…”
Section: Proposed Solutionmentioning
confidence: 98%
“…We refer the reader to the work of Bustos et al for details on their proposed algorithm. Bustos et al [2] found the constants a and b to be highly correlated, permitting the estimation of b in terms of a as…”
Section: Estimating Network Sizementioning
confidence: 98%
See 2 more Smart Citations
“…In order to apply such technique, we apparently need to know a local estimate of system size: this is a quite intriguing research problem [2]. We explore an alternative which consists in using the feedback that we obtain from the observed return times; using that feedback we locally control token generation or removal.…”
Section: Multiple Tokens Randomly Movingmentioning
confidence: 99%